Epithelium dynamics differ in time and space when exposed to the permeation enhancers penetramax and EGTA. A head-to-head mechanistic comparison - Panou, D. A.; Pedersen, S. F.; Kristensen, M.; Nielsen, H. M. (Frontiers in Drug Delivery, 2023)
Absorption of therapeutic peptides like glucagon-like peptide or insulin for diabetes therapy upon oral administration is highly restricted by the tight junction (TJ) proteins interconnecting the cells comprising the intestinal epithelium. An approach to improve transepithelial permeation of such biopharmaceuticals via the paracellular pathway is to use functional excipients, which transiently modulate the TJs. Here, we investigated the membrane-interacting peptide, penetramax, and the divalent cation chelator, ethylene glycol tetraacetic acid (EGTA) at different concentrations, to reveal and compare their cellular modes of action when increasing the transepithelial permeation of drug macromolecules. The epithelial integrity was studied in real time along with dextran permeation across differentiated epithelial Caco-2 cell monolayers. TJ protein expression and cytoskeleton organization were investigated during and after exposure to penetramax or EGTA. Based on orthogonal methods, we show that penetramax acts by a mechanism that immediately and transiently widens the paracellular space, resulting in size selective permeant passage and with subsequent reconstitution of the epithelium. At the same time, the expression and organization of different TJ proteins are modulated reversibly. In contrast, the effect of EGTA on modulating the paracellular space is slower and TJ protein unspecific, and without clear permeant size selectivity. Overall, these data provide in-depth insights for understanding intestinal barrier dynamics of importance when evaluating new or existing excipients for oral delivery of biopharmaceuticals, such as peptide therapeutics.